Evaluation of High Levels of Distillers Dried Grains with Solubles (DDGS) in Broiler Diets - Wang, Z.; Cerrate, S.; Coto, C.; Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2008)
A trial was conducted to evaluate high levels of distillers dried grains with solubles (DDGS) in broiler diets throughout a 49 d growing period. Diets were formulated based on digestible amino acid content to contain 0, 10, 20, 30, 40, or 50% DDGS. Diets were formulated to be optimum nutrient density commensurate with approximately 1% supplemental poultry oil. Each dietary treatment was assigned to four replicate pens with 25 commercial male broiler chicks. Starter (0-14 d) and grower (14-35 d) diets were fed as pellets with finisher (35-49 d) diets fed as mash. Bulk density (mass/volume) was determined on all the diets. Body weights and feed consumption were determined at 14, 35, 42 and 49 d of age. At the conclusion of the study, five representative birds per pen were processed to determine dressing percentage and parts yield. Generally, the bulk density of pellet or mash diets in all different growth periods decreased as DDGS inclusion rates increased, especially in mash diets. Level of DDGS had little effect on body weight at any age until up to 20% inclusion, after which body weight declined significantly. Feed intake was not significantly affected by level of DDGS during all the periods except of 0-14 d. For the whole period (0-49 d), the estimated metabolizable energy intake by chickens was less as DDGS inclusion increased. Increasing DDGS levels significantly increased calorie conversion ratio (CCR, calorie/gain ratio), especially during the period of 0-42 and 0-49 d. Dressing percentage decreased linearly with increasing DDGS levels from 0-50%. There was a significant reduction in breast meat or leg quarter yield as a percentage of live weight with increasing DDGS inclusion, while birds fed higher levels of DDGS had higher wings as percentage of live weight. These results indicate that up to 30% DDGS could be used in broiler diets if price was justified. Inclusion of high levels of DDGS reduces the bulk density and pellet quality and may be a major reason for reduced performance. Low energy density of DDGS diets is probably the limiting factor in meeting the energy needs of the chick.